Motivasi Belajar Siswa Kelas XII IPS 2 SMAN 3 Jember melalui Bimbingan KelompokPendekatan REBT - Yugo Tri Lestari, Salsabilla; Mutakin, Fakhruddin; Karamoy, Yurike Kinanthy (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
This research aims to "increase the learning motivation of class XI IPS 2 students through providing group guidance services using the REBT approach at SMAN 3 Jember". This research uses a Guidance and Counseling Action Research (PTBK) study to determine the increase in learning motivation after receiving Rational Emotive Behavior Therapy (REBT) approach group guidance services. This type of research uses qualitative research which relies on guidance and counseling action research which is carried out in 2 cycles and in each cycle there are three meetings. The data collection method used was observation, questionnaires and interviews with a sample of 5 members. Based on the results of the pre-cycle data, the low percentage was found to be 41% in the low category, after the first cycle of action it was found that 45% were still in the medium category, and in cycle II it increased to 80% in the high category. The conclusion is that providing REBT approach group guidance services can increase the learning motivation of class XI IPS 2 students at SMAN 3 Jember. It is hoped that further research will become reference material or research sources in developing study Keywords: Learning Motivation; REBT approach Group Guidance